Electric field-induced phase transitions in the hybrid halide perovskite MAPbI3 - Liljegren, Ylva (My University, 2026)
Hybrid halide perovskites have attracted significant attention due to their remarkable optoelectronic properties, which are sensitive to structural phase transitions. This work investigates electric field-induced phase transitions in methylammonium lead iodide (MAPbI3), a prototypical hybrid halide perovskite, using molecular dynamics simulations with a charge-aware neuroevolution potential. The structural and dynamical response of MAPbI3 to both static and oscillating electric fields is characterized across a range of temperatures, focusing on octahedral tilting, methylammonium (MA) cation orientations and vibrational properties. Under static fields up to 0.1V/Å, the orthorhombic-to-tetragonal phase transition temperature decreases while the tetragonal-to-cubic transition shifts to higher temperatures. Analysis of phonon mode projections indicates that electric fields induce a reorientation of the octahedral tilt pattern, with the dominant tilt axis preferentially oriented away from the field direction. A progressive alignment of MA molecular dipoles with increasing field strength is observed. For oscillating fields, frequency-temperature phase diagrams constructed for two field strengths reveal a substantial suppression of transition temperatures across many frequencies, with pronounced resonant features at 1.3 THz and 2.4 THz. Vibrational analysis suggests that these resonances couple to infrared-active PbI6 framework modes rather than direct MA dipole reorientation, providing insights into the intricate coupling between the inorganic lattice and organic cations that governs phase behavior under external fields.
Keywords: perovskites, phase transitions, electric fields, molecular dynamics, Born effective charges, neuroevolution potential